2016
DOI: 10.1539/joh.15-0140-br
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid concentrations in urine from chronic kidney disease patients in the North Central Region of Sri Lanka

Abstract: samples from the general population of Japan. Conclusions: Farmers (both with and without CKDu) living in CKDu-endemic areas in the NCR of Sri Lanka are exposed to lower neonicotinoid concentrations than non-occupationally exposed residents of Japan. (J Occup Health 2016; 58: 128−133)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…28 In a case control study, metabolites of neonicotinoid insecticides were shown to be lower in farmers with CKD compared to healthy controls living in Japan. 42 Aristolochic acid is a well-known nephrotoxin. 43 It's role in CKDu has not yet been evaluated adequately.…”
Section: Causative Factors -Human Studiesmentioning
confidence: 99%
“…28 In a case control study, metabolites of neonicotinoid insecticides were shown to be lower in farmers with CKD compared to healthy controls living in Japan. 42 Aristolochic acid is a well-known nephrotoxin. 43 It's role in CKDu has not yet been evaluated adequately.…”
Section: Causative Factors -Human Studiesmentioning
confidence: 99%
“…Biological monitoring has frequently detected imidacloprid in urine samples (Harada et al, 2016;Kabata et al, 2016;López-García et al, 2017;Ueyama et al, 2015;Ueyama et al, 2014;Yamamuro et al, 2014;Zhang et al, 2018); however, few studies have investigated its metabolites (Nomura et al, 2013;Uroz et al, 2001).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…; and in food matrices such as vegetables, fruits, honey and tea [4,10,19,23]. Also, some biomonitoring studies have consistently reported high detection frequencies of imidacloprid in human specimens and specimens from other non-target vertebrates [11,14,22,36,[39][40][41]46]. Despite these findings, little is known about the potential adverse health outcomes associated with chronic exposures to field realistic doses of imidacloprid in human populations.…”
Section: Introductionmentioning
confidence: 99%